Partikelverb och lexikon: kriterier för att finna lexikaliserade partikelverb - Norén, Kerstin (Nordiske Studier i Leksikografi, 1995)
This paper is an investigation of criteria which may be useful in deciding which phrasal verbs should be included in a dictionary. Most thoroughly scrutinized are syntactic and semantic criteria, and the conclusions are that semantic criteria combining the degree of localistic meaning and the specificity of valency ro les in a phrasal verb, are the most useful ones. This is due to the possibility of more or less quantifying the degree of lexicalization in the verb by using these semantic criteria.